Could COVID-19 be a latent viral infection? - Sergey Sheleg; Alexey Vasilevsky (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
COVID-19, a respiratory illness caused by a novel coronavirus, spread globally and emerged more than 6 million people by the beginning of June 2020.